2013
DOI: 10.1177/0268580913489323
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of educational credentials, changing economic returns, and rising occupational education requirements: Evidence in urban China from 2003 to 2008

Abstract: A remarkable expansion of secondary and tertiary education has been witnessed in mainland China in the past decades, resulting in changing returns to educational credentials. Using data from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…After completing secondary education, students have the choice of continuing their education at a four-year university or a three-year vocational college [18]. While a number of studies have focused on the effect of higher (vocational) education on Chinese youth [19,20], this study aimed to fill the gap by exploring the upper-secondary sector, which includes the vocational route (e.g., specialised schools, skilled-worker schools, and vocational secondary schools) and the general/academic route (e.g., general high schools).…”
Section: The Chinese Upper-secondary Systemmentioning
confidence: 99%
“…After completing secondary education, students have the choice of continuing their education at a four-year university or a three-year vocational college [18]. While a number of studies have focused on the effect of higher (vocational) education on Chinese youth [19,20], this study aimed to fill the gap by exploring the upper-secondary sector, which includes the vocational route (e.g., specialised schools, skilled-worker schools, and vocational secondary schools) and the general/academic route (e.g., general high schools).…”
Section: The Chinese Upper-secondary Systemmentioning
confidence: 99%
“…In recent years, the expansion of higher education in China has led to the expansion of academic qualifications, which has increased the supply of high-quality labor and directly increased the requirements of jobs for academic qualifications. From 2003 to 2008, the number of jobs requiring a university degree or above in China has increased sharply, which makes individuals with lower education have to accept lower wages and even withdraw from the labor market ( Hu, 2013 ). It can be seen that the increase in income brought by the improvement of individual education will reduce their economic dependence on their spouse, and the decrease in their economic dependence on their spouse will reduce their housework time.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…In the Chinese Reform Era, educational credentials are used as a tool to distinguish between job applicants in an increasingly competitive market (Hansen and Woronov 2013). Hu's (2013) research on the Chinese labour market between 2003 and 2008 demonstrated a significant increase in the number of jobs requiring post-secondary credentials in that period, as well as a significant decline in the economic returns for a post-secondary credential. The comparative advantages of vocational college graduates in the labour market are not apparent, and they are easily overtaken by university graduates (Ding 2004;Zhang 2008).…”
Section: Neoliberalism Human Capital and The Quest For Better Credent...mentioning
confidence: 99%